Answer:
Step-by-step explanation:24,000
。☆✼★ ━━━━━━━━━━━━━━ ☾
Divide by 3 on both sides
Have A Nice Day ❤
Stay Brainly! ヅ
- Ally ✧
。☆✼★ ━━━━━━━━━━━━━━ ☾
Answer:
x=−2
Step-by-step explanation: Step 1: Simplify both sides of the equation.
3(x−5)−3=5(x−2)+2x
(3)(x)+(3)(−5)+−3=(5)(x)+(5)(−2)+2x(Distribute)
3x+−15+−3=5x+−10+2x
(3x)+(−15+−3)=(5x+2x)+(−10)(Combine Like Terms)
3x+−18=7x+−10
3x−18=7x−10
Step 2: Subtract 7x from both sides.
3x−18−7x=7x−10−7x
−4x−18=−10
Step 3: Add 18 to both sides.
−4x−18+18=−10+18
−4x=8
Step 4: Divide both sides by -4.
−4x
−4
=
8
−4
x=−2
Answer:
![V=312\pi\ mm^{3}](https://tex.z-dn.net/?f=V%3D312%5Cpi%5C%20mm%5E%7B3%7D)
Step-by-step explanation:
we know that
The volume of the composite figure is equal to the volume of a semi-sphere plus the volume of the cone
so
![V=\frac{4}{6}\pi r^{3} +\frac{1}{3} \pi r^{2} h](https://tex.z-dn.net/?f=V%3D%5Cfrac%7B4%7D%7B6%7D%5Cpi%20r%5E%7B3%7D%20%2B%5Cfrac%7B1%7D%7B3%7D%20%5Cpi%20r%5E%7B2%7D%20h)
we have
![r=6\ mm](https://tex.z-dn.net/?f=r%3D6%5C%20mm)
![h=14\ mm](https://tex.z-dn.net/?f=h%3D14%5C%20mm)
substitute
![V=\frac{4}{6}\pi (6)^{3} +\frac{1}{3} \pi (6)^{2} (14)](https://tex.z-dn.net/?f=V%3D%5Cfrac%7B4%7D%7B6%7D%5Cpi%20%286%29%5E%7B3%7D%20%2B%5Cfrac%7B1%7D%7B3%7D%20%5Cpi%20%286%29%5E%7B2%7D%20%2814%29)
![V=144\pi +168\pi](https://tex.z-dn.net/?f=V%3D144%5Cpi%20%2B168%5Cpi)
![V=312\pi\ mm^{3}](https://tex.z-dn.net/?f=V%3D312%5Cpi%5C%20mm%5E%7B3%7D)
Answer:
B) 12
Step-by-step explanation:
Opposite sides are congruent